DINAMIKA PERTUMBUHAN DAUN BIBIT STEK PUCUK STEVIA MENGGUNAKAN PUPUK KANDANG KOTORAN AYAM PADA TANAH GAMBUT - Djoko Eko Hadi Susilo (Anterior Jurnal, 2017)
The cultivation of stevia (Stevia rebaudiana Bertoni M.) in peat soil is necessary to find the substitution of sugar needs and as an alternative natural sweeteners. The aim of this study is to know how the the dynamics of leaf growth of germ of cutting of the shoot stevia on using the chicken manure fertilizer in peat soil. The results of this study are expected as a material of the study to support the development of cultivation of Stevia in the peat soil. This study was conducted using a polybag on Wortel street area, Panarung of the District of Pahandut of the Palangka Raya city from April to May 2017. The data of the observation were collected to the leaf growth (number of leaf and leaf area) of germ of cutting of the shoot stevia plant at the age of germ on 10 and 20 days after planting (DAP). The results of the study showed that the using of chicken manure fertilizer by the dosage 20 tons ha-1 until 40 tons ha-1 can increasing the dynamics of leaf growth (number of leaf and leaf area) of germ of cutting of the shoot stevia plant at the age of germ on 10 and 20 days after planting (DAP) in peat soil. The result of this study also requires further detailed study on the weight area ratio and spesific leaf area for cutting of the shoot stevia.